2015
DOI: 10.1038/nature14602
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubes mediate niche–stem-cell signalling in the Drosophila testis

Abstract: Stem cell niches provide resident stem cells with signals that specify their identity. Niche signals act over a short-range such that only stem cells but not their differentiating progeny receive the self-renewing signals1. However, the cellular mechanisms that limit niche signaling to stem cells remain poorly understood. Here we show that the Drosophila male germline stem cells (GSCs) form previously unrecognized structures, microtubule-based (MT)-nanotubes, which extend into the hub, a major niche component.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
189
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(200 citation statements)
references
References 35 publications
7
189
1
Order By: Relevance
“…The stem cell niche may provide such an example. Indeed, the formation of a nanotube network to induce a precise local induction of signaling between stem cells and supporting cells has been shown to regulate stem cell behavior (Inaba et al, 2015). A recent study has revealed the importance of the niche architecture as well as of paracrine Wnt signaling, which regulates cell behavior in a wide variety of cell lineages (Wabik and Jones, 2015).…”
Section: Cytonemes In the Stem Cell Nichementioning
confidence: 99%
“…The stem cell niche may provide such an example. Indeed, the formation of a nanotube network to induce a precise local induction of signaling between stem cells and supporting cells has been shown to regulate stem cell behavior (Inaba et al, 2015). A recent study has revealed the importance of the niche architecture as well as of paracrine Wnt signaling, which regulates cell behavior in a wide variety of cell lineages (Wabik and Jones, 2015).…”
Section: Cytonemes In the Stem Cell Nichementioning
confidence: 99%
“…Retrograde IFT occurs over a distance of about 209 nm and moves along A-microtubules (Pigino et al, 2009;Stepanek and Pigino, 2016). In addition, IFT proteins also function in other cellular processes, including vesicle exocytosis, cell division and the formation of immunological synapses and microtubule-based nanotubes (Baldari and Rosenbaum, 2010;Borovina and Ciruna, 2013;Griffiths et al, 2010;Inaba et al, 2015;Wood et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include Drosophila male germline stem cells, in which daughter cells require physical contact with the hub (a group of supporting cells) to maintain stemness (Inaba et al, 2015;Yamashita et al, 2005). During stomatal development, EPF1-ERL1/TMM peptide-receptor kinase signaling is required to orient the polarity of the asymmetric spacing divisions .…”
Section: Signal Integration Controlling Upstream Signaling Ligandsmentioning
confidence: 99%